2020
DOI: 10.1002/jcp.29738
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell line‐derived neurotrophic factor alters lipid composition and protein distribution in MPP+‐injured differentiated SH‐SY5Y cells

Abstract: Parkinson's disease (PD) is a neurodegenerative disease characterized by progressive loss of dopaminergic neurons in the substantia nigra and striatum. Glial cell line‐derived neurotrophic factor (GDNF) can effectively promote the differentiation and survival of many types of neurons, especially dopaminergic neurons, suggesting it could be a treatment for PD. Lipid rafts are highly dynamic cell membrane domains that contain numerous signal protein receptors, providing an important platform for signal transduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…It has been shown that, in a variety of neurodegenerative diseases, such as PD, Alzheimer's disease and familial amyotrophic lateral sclerosis, lipid rafts appear to have abnormal lipid composition and functional de ciencies in the brain, which can promote the pathogenesis and development of these diseases [36][37][38] . Our previous study also showed that the lipid and protein components of lipid rafts were signi cantly altered in MPP + -induced PD cell models [39] . Furthermore, studies of various unit membrane models have shown that GM1 can affect the phase separation of lipid membranes and the assembly of microdomains [22,24,40,41] .…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that, in a variety of neurodegenerative diseases, such as PD, Alzheimer's disease and familial amyotrophic lateral sclerosis, lipid rafts appear to have abnormal lipid composition and functional de ciencies in the brain, which can promote the pathogenesis and development of these diseases [36][37][38] . Our previous study also showed that the lipid and protein components of lipid rafts were signi cantly altered in MPP + -induced PD cell models [39] . Furthermore, studies of various unit membrane models have shown that GM1 can affect the phase separation of lipid membranes and the assembly of microdomains [22,24,40,41] .…”
Section: Discussionmentioning
confidence: 82%
“…20,21) Some secreted factors are known to affect the lipid composition of the brain. [22][23][24] Among those factors, a secreted glycoprotein Reelin contributes to increased levels of polyunsaturated fatty acids in neurons, 23) which may partly explain why Reelin induces dendrite elongation. [25][26][27] However, how neurons regulate plasma membrane polarity is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…GDNF is a family of neurotrophins with similarities to the transforming growth factor β regulatory proteins ( 11 , 35 ) and it has been identified as a potent neurotrophic factor for a variety of neuronal cell populations ( 36 ). GDNF is biosynthesized in glial cells and might be relevant to the development of gliomas ( 37 ).…”
Section: Discussionmentioning
confidence: 99%